Mohd Shukor retains PBBM Chief post - Daily Express, (KK) (Daily Express (KK), 2014)
KOTA KINABALU: The Malaysian Statutory Bodies Association (PBBM) President, Tan Sri Dr Mohd Shukor Mahfar, and VicePresident, Prof Datuk Dr Abdullah Mohamed Said, from University Teknologi Mara (UiTM) will retain their positions for the 2014-2016 session.